A Review of MAL-PDT for the Treatment Strategy of Actinic Keratosis: Broader Clinical Perspectives Beyond the Data and Guideline Recommendations - Rolf-Markus Szeimies; Thomas Dirschka; Maria Concetta Fargnoli; Yolanda Gilaberte; Merete Hædersdal; Rajeev Chavda; Piergiacomo Calzavara-Pinton (Dermatology and Therapy, 2023)
Abstract Methyl aminolevulinate (MAL) is a topical compound approved for use with photodynamic therapy (PDT) for the treatment of actinic keratosis (AK) and field cancerization in certain countries. There exists a high burden of disease for patients with AK: repeated treatments are required, there is a known risk of progression to keratinocyte carcinoma, and cosmetic appearance is affected. Delivery of PDT using MAL is a flexible treatment strategy available in many forms; red light, daylight, or artificial daylight can be used for illumination, all of which result in high AK clearance rates and low recurrence. MAL-PDT protocols continue to evolve to further improve adherence and treatment outcomes. Here, we used PubMed to search MEDLINE to identify guidelines, consensus recommendations, and studies describing the use of MAL for the treatment of AK. The aim of this targeted review is to consider various MAL-PDT treatment strategies on the basis of published literature, with a focus on personalizing treatment for the heterogeneous AK population.